Effect of parenteral glutamine supplementation combined with enteral nutrition on Hsp90 expression and lymphoid organ apoptosis in severely burned rats - Fan, Jun; Wu, Jing; Wu, Li-dong; Li, Guo-ping; Xiong, Meng; Chen, Xi; Meng, Qing-yan (Burns, 2016)
•We studied the effects of glutamine combined with enteral nutrition on immune function in burned rats.•Glutamine combined with enteral nutrition enhanced Hsp90 expression in lymphatic organs in burned rats.•Glutamine combined with enteral nutrition attenuated lymphatic organ apoptosis in burned rats.•Glutamine combined with enteral nutrition improved the humoral and cellular immunity in burned rats. The aim of this study is to investigate the effects of parenteral glutamine(GLN) supplementation combined with enteral nutrition (EN) on heat shock protein 90(Hsp90) expression, apoptosis of lymphoid organs and circulating lymphocytes, immunological function and survival in severely burned rats. Male SD rats were randomly assigned into 4 groups: a sham burn+EN+GLN-free amino acid (AA) group (n=10), a sham burn+EN+GLN group (n=10), a burn+EN+AA group (n=10), and a burn +EN +GLN group (n=10). Two hours after a 30% total body surface area (TBSA), full-thickness scald burn injury on the back was made, the burned rats in two experimental groups (the burn+EN+AA group and the burn+EN +GLN group) were fed with a conventional enteral nutrition solution by oral gavage for 7 days. Simultaneously, the rats in the burn+EN+GLN group were given 0.35g GLN/kg body weight/day once via a tail vein injection for 7 days, whereas those in the burn+EN+AA group were administered isocaloric/isonitrogenous GLN-free amino acid solution (Tyrosine) for comparison. The rats in two sham burn control groups (the sham burn+EN+AA group and the sham burn+EN +GLN group) were treated in the same procedure as above, except for burn injury. All rats in each of the four groups were given 175kcal/kg body wt/day. There was isonitrogenous, isovolumic and isocaloric intake among four groups. At the end of the 7th day after nutritional programme were finished, all rats were anesthetized and samples were collected for further analysis. Serum immunoglobulin quantification was conducted by ELISA. Circulating lymphocyte numbers were counted by Coulter LH-750 Analyzer. The percentages and apoptotic ratio of CD4 and CD8T lymphocytes in circulation were determined by flow cytometry (FCM). The neutrophil phagocytosis index (NPI) was examined. The GLN concentrations in plasma, thymus, spleen and skeletal muscle were measured by high performance liquid chromatography (HPLC). The organ index evaluation and TUNEL analysis of thymus and spleen were carried out. The expression of Hsp90 in thymus and spleen was analyzed by western blotting. Moreover, the survival in burned rats was observed. The results revealed that parenteral GLN supplementation combined with EN significantly increased the GLN concentrations of plasma and tissues, the serum immunoglobulin content, the circulating lymphocyte number, the CD4/CD8 ratio, the indexes of thymus and spleen, NPI and survival as compared with the burn+EN+AA group (p<0.05). The expression of Hsp90 in thymus and spleen in the burn+EN+GLN group was significantly up-regulated as compared with the burn+EN+AA group (p<0.05). The apoptosis in circulating CD4 and CD8 lymphocytes, thymus and spleen in the burn+EN+GLN group was significantly decreased as compared with the burn+EN+AA group (p<0.05). The results of this study show that parenteral GLN supplementation combined with EN may increase the GLN concentrations of plasma and tissues, up-regulate the expression of Hsp90, attenuate apoptosis in lymphoid organ and circulating lymphocyte, enhance the immunological function and improve survival in severely burned rats. Clinically, therapeutic efforts at the modulation of the immune dysfunction may contribute to a favorable outcome in severely burned patients.